Pengaruh Tata Ruang Kelas Terhadap Konsentrasi dan Partisipasi Belajar Siswa - Putri Aulia Liliatis Sa’adah; Iftitahur Rizqi Amaliyah; Ananda Lailatul Kholifah (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to determine the influence of classroom layout on students’ concentration and participation during the learning process. This research used a descriptive qualitative method, with teachers and students in the school environment as the research subjects. Data were collected through observation, interviews, and documentation. The results showed that classroom layout has a significant influence on students’ comfort, concentration, and learning participation. Classrooms with good lighting, adequate ventilation, maintained cleanliness, and seating arrangements that support interaction can create a more conducive learning atmosphere. Students become more focused in receiving learning materials and more active in asking questions and participating in discussions. Conversely, poorly arranged classroom conditions cause students to lose attention easily and become less involved in learning activities. In addition, teachers also play an important role in arranging the classroom layout according to learning needs. Based on the results of the study, it can be concluded that classroom layout is one of the important factors that supports the effectiveness of the teaching and learning process and improves the quality of student learning at school.